Effect of Cyclic Heat Stress on Hypothalamic Oxygen Homeostasis and Inflammatory State in the Jungle Fowl and Three Broiler-Based Research Lines - Brugaletta, Giorgio; Greene, Elizabeth; Ramser, Alison; Maynard, Craig W.; Tabler, Travis W.; Sirri, Federico; Anthony, Nicholas B.; Orlowski, Sara; Dridi, Sami (Frontiers in Veterinary Science, 2022)
The present study aimed, therefore, to determine the hypothalamic expression of a newly involved pathway, hypoxia/oxygen homeostasis, in heat-stressed broiler-based research lines and jungle fowl. Three populations of broilers (slow growing ACRB developed in 1956, moderate growing 95RB from broilers available in 1995, and modern fast growing MRB from 2015) and unselected Jungle fowl birds were exposed to cyclic heat stress (36°C, 9h/day for 4 weeks) in a 2x4 factorial experimental design. Total RNAs and proteins were extracted from the hypothalamic tissues and the expression of target genes and proteins was determined by real-time quantitative PCR and Western blot, respectively. HS increased core body temperature and decreased feed intake in 95RB and MRB, but not in ACRB or JF (Tabler, 2020). HS exposure did not affect the hypothalamic expression of HIF complex, however there was a line effect for HIF-1α (P = 0.02) with higher expression in JF under heat stress. HS significantly up regulated the hypothalamic expression of hemoglobin subunits (HBA1, HBBR, HBE, HBZ), and HJV in ACRB, HBA1 and HJV in 95RB and MRB, and HJV in JF, but it down regulated FPN1 in JF. Additionally, HS altered the hypothalamic expression of oxygen homeostasis- up and down-stream signaling cascades. Phospho-AMPKThr172 was activated by HS in JF hypothalamus, but it decreased in that of the broiler-based research lines. Under thermoneutral conditions, p-AMPKThr172 was higher in broiler-based research lines compared to JF. Ribosomal protein S6K1, however, was significantly upregulated in 95RB and MRB under both environmental conditions. HS significantly upregulated the hypothalamic expression of NF-κB2 in MRB, RelB and TNFα in ACRB, abut it down regulated RelA in 95RB. The regulation of HSPs by HS seems to be family- and line-dependent. HS upregulated the hypothalamic expression of HSP60 in ACRB and 95RB, down regulated HSP90 in JF only, and decreased HSP70 in all studied lines. Taken together, this is the first report showing that HS modulated the hypothalamic expression of hypoxia- and oxygen homeostasis-associated genes as well as their up- and down-stream mediators in chickens, and suggests that hypoxia, thermotolerance, and feed intake are interconnected, which merit further in-depth investigations.